How Not to Be Seen: Notes on the Gendered Intimacy of Livestreaming the Covid-19 Pandemic. (July 2022) - Lark, Daniel
Livestreaming during the Covid-19 pandemic has become a staging ground for a kind of virtual socialization that favors gendered and middle class norms of intimacy, affective labor, and domesticity, despite a grave lack of material support for the transition to online learning and working from home. In this paper, I focus on key images and discussions circulating in the press and on social media around the performance and construction of the livestreaming space in relation to virtual learning and remote work among white collar professionals. Livestreaming reshapes domestic life and space through its ability to blur the boundary between home and work and the nascent norms and practices of livestreaming borrow from existing streaming subcultures such as video game streaming on platforms like Twitch.tv. The intimacy of livestreaming, however, is a double-edged sword as it exposes livestreaming's inability to curtail the worst effects of the pandemic and the disproportionate impact of this vast social rearrangement on women. Livestreaming is easily integrated into existing regimes of control and is the subject of an intense public debate about its politics this very reason.